2016
DOI: 10.1016/j.apenergy.2015.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting sparsity of interconnections in spatio-temporal wind speed forecasting using Wavelet Transform

Abstract: Integration of renewable energy resources into the power grid is essential in achieving the envisioned sustainable energy future. Stochasticity and intermittency characteristics of renewable energies, however, present challenges for integrating these resources into the existing grid in a large scale. Reliable renewable energy integration is facilitated by accurate wind forecasts. In this paper, we propose a novel wind speed forecasting method which first utilizes Wavelet Transform (WT) for decomposition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…Zhou et al [48] proposed a spatial and temporal correlation model and it was found that this model could improve ultra-short-term wind power forecasting accuracy. Tascikaraoglu et al [49] proposed a novel method, which first utilized a Wavelet Transform (WT) method to decompose the wind speed data into more stationary components and then used a spatio-temporal model on each of the subseries to incorporate both the temporal and spatial information for wind speed forecasting. Ye et al [50] analyzed uncertainty and dependence in wind power output, and employed a physical spatio-temporal correlation model.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [48] proposed a spatial and temporal correlation model and it was found that this model could improve ultra-short-term wind power forecasting accuracy. Tascikaraoglu et al [49] proposed a novel method, which first utilized a Wavelet Transform (WT) method to decompose the wind speed data into more stationary components and then used a spatio-temporal model on each of the subseries to incorporate both the temporal and spatial information for wind speed forecasting. Ye et al [50] analyzed uncertainty and dependence in wind power output, and employed a physical spatio-temporal correlation model.…”
Section: Introductionmentioning
confidence: 99%
“…Tascikaraoglu et al [251] used WT method to efficiently capture wind speed data stationary components, which were subsequently translated into more accurate wind forecast via compressive spatio-temporal wind speed forecasting (CST-WSF) model. In addition, Wang and Hu [252] developed a multiplemodel framework comprising of empirical wavelet transform (EWT), ARIMA, LSSVM, ELM, SVM and Gaussian Process Regression (GPR) models for forecast reliability and robustness enhancement.…”
Section: Referencesmentioning
confidence: 99%
“…Spatial correlation models [13] Obtaining a satisfactory wind speed forecasting by vast quantities of information that need be considered and collected [13].…”
Section: Spatial Correlation Modelsmentioning
confidence: 99%